2018
DOI: 10.1111/jocn.14202
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of deterioration and patient and family activated escalation systems—A qualitative study

Abstract: Aims and objectives: To investigate the experiences of patients who received a medical emergency team review following a period of clinical deterioration and their views about the potential use of a patient and family activated escalation system.Background: Delay or failure by health professionals to respond to clinical deterio-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 47 publications
(60 reference statements)
0
55
0
2
Order By: Relevance
“…Norms of passivity, language and health literacy have been described to influence patient and family's willingness and ability to actively speak up in similar situations. It has also been suggested that families' reticence to speak up is associated with confidence and familiarity with the health‐care system . In this study, difficulty speaking up was also described by parents who were themselves highly health literate health professionals who wanted to avoid conflict with colleagues.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Norms of passivity, language and health literacy have been described to influence patient and family's willingness and ability to actively speak up in similar situations. It has also been suggested that families' reticence to speak up is associated with confidence and familiarity with the health‐care system . In this study, difficulty speaking up was also described by parents who were themselves highly health literate health professionals who wanted to avoid conflict with colleagues.…”
Section: Discussionmentioning
confidence: 74%
“…It has also been suggested that families' reticence to speak up is associated with confidence and familiarity with the health-care system. 12,15 In this study, difficulty speaking up was also described by parents who were themselves highly health literate health professionals who wanted to avoid conflict with colleagues. At this point, no specific strategies had been used to address the barrier of overcoming the traditional hospital hierarchy which remains a widely reported issue in escalation of care.…”
Section: Thismentioning
confidence: 91%
See 2 more Smart Citations
“…Five qualitative studies were included in the review, consisting of the experiences of 88 patients and 32 relatives reported in four studies 35–38 . One study 39 reported on the experiences and views of patients, relatives, and healthcare staff, however, did not clearly report on the sample size from each group (n = 56).…”
Section: The Reviewmentioning
confidence: 99%